Clinical and Psychological Aspects of the Bereavement and Diagnostic of Complicated Grief - Oleksandr Avramchuk (Проблеми сучасної психології, 2019)
The actual studies of scientific and psychological approaches to the concept of experiencing bereavement and complicated grief are considered in the article. It is emphasized that the optimal trajectory of recovery after the death of a significant person consists in the successful resolution of nonlinear «tasks», caused by the loss, and passes with minor functional impairments, involves effective coping strategies and activities that allow a healthy way of expressing emotions, remembering the deceased and overcome current life problems. The information on clinical and psychological features and diagnostic signs of complicated grief are generalized. It is proved that the core of the complicated grief is a complex of symptoms of intense and persistent separation distress, which does not lead to the elaboration of the experience of loss, but is replaced by stereotyped, repeated thinking strategies and behavior strategies, which increase psychosocial disturbances. The diagnostic criteria for the difference between healthy and pathological (complicated) grief, covering the intensity, duration, and complexity of symptoms are identified. The relevance and complexity of the differential diagnosis of complicated grief among other bereavement-related mental health disorders are emphasized. It is noted that due to the communion of a clinical picture with a major depressive disorder and post-traumatic stress disorder, people with complicated grief remain inadequately diagnosed or misdiagnosed, and that leads to the using of treatment as usual that partly reduces comorbid symptoms without affecting the complicated grief symptoms. The differences between complicated grief, major depressive disorder, and post-traumatic stress disorder are generalized, which may be useful for differential diagnosis by mental health professionals. The author concluded that there is a need to develop educational and training programs directed at increasing professional knowledge and competencies in diagnostics and differential diagnostics of complicated grief and adaptation of screening methods for assessing complicated grief in Ukraine.